(untitled) (Economics and region, 2024)
The article focuses on economic security in the People’s Republic of China (PRC), research activities in this field, as well as the system of state governance, legislation, and legal system of the PRC aimed at ensuring and managing economic security at various hierarchical levels. The subject of the research is the Constitution of the People’s Republic of China, laws, and subordinate normative legal acts reflecting aspects of national security of the People’s Republic of China, conducted by Chinese scholars in the field of China’s economic security. The object of the study is the concept and definition of economic security in the academic sphere in China, patterns and trends in the development of social relations in the PRC in the process of ensuring national security and economic security of the country. The author extensively examines various aspects of the topic, such as different approaches to the concept of economic security among Chinese researchers, components of the overall economic security system and its subsystems, as well as their interactions, and regulatory acts governing national security issues in the country. Special attention is paid to the potential use of the results of this research for comparative analysis in conducting other similar studies. The methodological basis is the dialectical method of cognition, within which a combination of general scientific methods (historical, logical analysis and synthesis) and specific scientific methods (comparative legal analysis, content analysis, etc.) is applied for theoretical research. The study on the national economic security of the People’s Republic of China has been conducted and discussed, where the authors examine the concept of economic security from various perspectives and identify economic sectors and corresponding indicators deemed most important and vulnerable in terms of national security. The main conclusions of the study suggest that taking into account the nuances of interpreting and perceiving economic security in the academic sphere of China, as well as the administrative and legal provision of national security in the PRC, will contribute to the improvement of scientific research and legislative activities of other countries in this field. Furthermore, it will lead to a clearer definition of theoretical concepts and practical activities in the sphere of economic security of the state. Additionally, resolving common issues related to ensuring national security from the perspective of state governance will be facilitated.